Identification of SNPs in MITF associated with beak color of duck - Pan, Rui; Hua, Tian; Guo, Qixin; Bai, Hao; Jiang, Yong; Wang, Zhixiu; Bi, Yulin; Chen, Guohong; Wu, Xinsheng; Chang, Guobin (Frontiers in Genetics, 2023)
Beak color-a pigment-related trait-is an important feature of duck breeds. To investigate the genetic mechanism of beak colors, we conducted an integrated analysis of genomic selection signatures to identify a candidate site associated with beak color. For this, we used black-billed (Yiyang I meat duck synthetic line H1, H2, H3, and HF) and yellow-billed ducks (Cherry Valley ducks and white feather Putian black duck). Quantitative real-time PCR and genotyping approaches were used to verify the function of the candidate site. As a result, we identified 3895 windows containing 509 genes. After GO and KEGG enrichment analysis, 9 genes were selected. Ultimately, MITF was selected by comparing the genomic differentiation (FST). After loci information selection, 41 extreme significantly different loci were selected, which are all located in intron regions of MITF and are in almost complete linkage disequilibrium. Subsequently, the site ASM874695v1:10:g.17814522T>A in MITF was selected as the marker site. Furthermore, we found that MITF expression is significantly higher in black-beaked ducks than in yellow-beaked ducks of the F2 generation (P<0.01). After genotyping, most yellow-billed individuals are found with homozygous variant; at the same time, there are no birds with homozygous variant in black-billed populations, while the birds with homozygous and heterozygous variant share the same proportion. Thus, MITF plays a very critical role in the melanogenesis and melanin deposition of duck beaks, which can effectively affect the beak color. The MITF site, ASM874695v1:10:g.17814522T>A could be selected as a marker site for the duck beak color phenotype.